2017
DOI: 10.1002/bsl.2290
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Reported Current Practices in Child Forensic Interviewing: Training, Tools, and Pre‐Interview Preparation

Abstract: In child sexual abuse investigations, forensic interviewers within the Child Advocacy Center (CAC) model serve as neutral fact-finders for a team of professionals tasked with investigating and intervening in cases of alleged child sexual abuse. Although empirical evidence has led to the development of best-practice techniques and protocols, there is currently no universally adopted protocol in the field. The present research gathered detailed information from a national sample of real-world child forensic inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 25 publications
(33 reference statements)
5
30
0
Order By: Relevance
“…Furthermore, 21% of the professionals reported that they did not use a standardized method for conducting child investigative interviews, 22% reported using multiple methods, and 87% indicated different professionals apply different methods at their Safe Home organization. This lack of a standardized child forensic interviewing method concurs with recent research among child protection professionals in the USA (Rivard and Compo, 2017). Rivard and Compo (2017) created an online survey which was distributed among Child Advocacy Centres and other child sexual abuse investigative agencies throughout the United States.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Furthermore, 21% of the professionals reported that they did not use a standardized method for conducting child investigative interviews, 22% reported using multiple methods, and 87% indicated different professionals apply different methods at their Safe Home organization. This lack of a standardized child forensic interviewing method concurs with recent research among child protection professionals in the USA (Rivard and Compo, 2017). Rivard and Compo (2017) created an online survey which was distributed among Child Advocacy Centres and other child sexual abuse investigative agencies throughout the United States.…”
Section: Discussionsupporting
confidence: 59%
“…This lack of a standardized child forensic interviewing method concurs with recent research among child protection professionals in the USA (Rivard and Compo, 2017). Rivard and Compo (2017) created an online survey which was distributed among Child Advocacy Centres and other child sexual abuse investigative agencies throughout the United States. This study also showed a diversity of interviewing protocols across agencies and professionals were trained in different methods.…”
Section: Discussionsupporting
confidence: 59%
“…After contacting over 2,000 police and sheriff’s departments, the final sample included a diverse array of United States law enforcement professionals ranking from chief of police to polygraph examiner ( N = 388; see Table 1). This recruitment yield is similar to that in previous related studies (e.g., Rivard and Schreiber Compo, 2017; Shaffer and Evans, 2018). A third of the sample reported having been at their current rank for 1–3 years, while 22% reported having been at their current rank for 4–7 years, 10% reported having been at their current rank for 8–10 years and 25% reported to have been at their current rank for over 10 years.…”
Section: Methodssupporting
confidence: 90%
“…Outlines can be created during this stage of the process. However, it is important to know that previous disclosures and allegations will likely be known at this stage and interviewers will need to use caution not to allow outlines to become sources of contamination and suggestion (Rivard & Compo, 2017). Consistent with this warning, pre-interview preparation remains controversial (Fessinger & McAuliff, 2020), and some experimental studies (Rivard et al, 2016) and legal cases ( Idaho v. Wright , 1990) have argued against it in favor of allegation-blind interviewing.…”
Section: Applying Research To Practice: Note-taking Strategies For the Forensic Interviewermentioning
confidence: 99%
“…First, the most pressing need in terms of research is to systematically examine the rates and perceptions of note-taking by forensic interviewers and child interviewees. In their survey of forensic interviewers, Rivard and Compo (2017) found that 62.5% of forensic interviewers in their sample ( N = 160) reported taking notes during forensic interviews. If this percentage is representative of forensic interviewing practices across North America, it would indicate that more than half of forensic interviewers are employing note-taking during their interviews.…”
Section: Future Research Recommendationsmentioning
confidence: 99%